Blood oxytocin concentration positively predicts contagious yawning behavior in children with autism spectrum disorder. Issue 8 (27th May 2019) - Mariscal, Michael G.; Oztan, Ozge; Rose, Sophie M.; Libove, Robin A.; Jackson, Lisa P.; Sumiyoshi, Raena D.; Trujillo, Tara H.; Carson, Dean S.; Phillips, Jennifer M.; Garner, Joseph P.; Hardan, Antonio Y.; Parker, Karen J.
Abstract : Research suggests that children with autism spectrum disorder (ASD) may have reduced empathy, as measured by an impaired contagious yawn response, compared to typically developing (TD) children. Other research has failed to replicate this finding, instead attributing this phenomenon to group differences in attention paid to yawn stimuli. A third possibility is that only a subgroup of children with ASD exhibits the impaired contagious yawn response, and that it can be identified biologically. Here we quantified blood concentrations of the "social" neuropeptide oxytocin (OXT) and evaluated yawning behavior and attention rates during a laboratory task in children with ASD ( N  = 34) and TD children ( N  = 30) aged 6–12 years. No group difference in contagious yawning behavior was found. However, a blood OXT concentration × group (ASD vs. TD) interaction positively predicted contagious yawning behavior ( F 1, 50  = 7.4987; P  = 0.0085). Specifically, blood OXT concentration was positively related to contagious yawning behavior in children with ASD, but not in TD children. This finding was not due to delayed perception of yawn stimuli and was observed whether attention paid to test stimuli and clinical symptom severity were included in the analysis or not. These findings suggest that only a biologically defined subset of children with ASD exhibits reduced empathy, as measured by the impaired contagious yawn response, and that prior conflicting reports of this behavioral phenomenon may be attributable, at least in part, to variable mean OXT concentrations across different ASD study cohorts. Autism Res 2019, 12: 1156–1161 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: People with autism may contagiously yawn (i.e., yawn in response to another's yawn) less often than people without autism. We find that people with autism who have lower levels of blood oxytocin (OXT), a hormone involved in social behavior and empathy, show decreased contagious yawning, but those who have higher blood OXT levels do not differ in contagious yawning from controls. This suggests that decreased contagious yawning may only occur in a biologically defined subset of people with autism.